TOWED SPECTRA OF INTERNAL WAVES IN THE PYCNOCLINE OF THE BALTIC SEA - Morozov E.G.; Shchuka S.A.; Zapotyl'Ko V.S. (My University, 2007)
The data on temperature and salinity measurements with a towed temperature and salinity profiler operated in scanning mode in the pycnocline between the Baltic (surface) waters and transformed inflow (deep) waters of the North Sea origin in the Gdansk Deep of the Baltic Sea are analyzed. The measurements were carried out on March 3, 2006. It is shown that the spectral level of vertical displacements is below the background Garrett–Munk spectrum. Such an effect is explained by the absence of tides in the hydrological regime of the Baltic Sea.